2020
DOI: 10.1029/2019jb018145
|View full text |Cite
|
Sign up to set email alerts
|

On the Broadband Instrument Response of Fiber‐Optic DAS Arrays

Abstract: Distributed Acoustic Sensing (DAS) is a novel tool in array seismology that measures the phase of backscattered laser pulses traveling in a fiber‐optic cable, and relates this measurement to the axial strain induced on the cable by a propagating seismic wavefield. Combining DAS with telecommunications optical fiber networks has begun to address a range of earth science questions where cost and field logistics have historically hindered observations. Unlike classic inertial seismometers, DAS instrument response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
169
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(174 citation statements)
references
References 43 publications
5
169
0
Order By: Relevance
“…To verify that this DAS system (interrogator, fiber, and cable in conduit) records a useful metric of ground motion, we convert our DAS recordings to particle velocity and compare to the nearest broadband seismometer. This calibration procedure is based on several previous studies (Daley et al, 2016;Wang et al, 2018;Lindsey et al, 2020a). To ensure this paper is self-contained, we briefly review this procedure.…”
Section: Das Calibration To Seismometersmentioning
confidence: 99%
See 3 more Smart Citations
“…To verify that this DAS system (interrogator, fiber, and cable in conduit) records a useful metric of ground motion, we convert our DAS recordings to particle velocity and compare to the nearest broadband seismometer. This calibration procedure is based on several previous studies (Daley et al, 2016;Wang et al, 2018;Lindsey et al, 2020a). To ensure this paper is self-contained, we briefly review this procedure.…”
Section: Das Calibration To Seismometersmentioning
confidence: 99%
“…We assume refractive index changes linearly with strain rate ( ∆n n = (ζ −1) ∆x x ). The scalar multiplicative factor (ζ) is determined by the material properties: ζ = 0.735 for single-mode fiber glass with light propagating inside (Lindsey et al, 2020a). Hence the phase changes at the same 4 https://doi.org/10.5194/se-2020-103 Preprint.…”
Section: Das Calibration To Seismometersmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al (2018) have demonstrated the similarity between DAS and seismograph strain measurements, and confirmed that the observed signal is axial strain along a fiber-optic cable in the ordinary frequency range for seismic observations (i.e., several Hertz). At lower frequencies, Ajo-Franklin et al (2019) observed the surface waves from large teleseismic earthquakes, and Lindsey et al (2020) demonstrated how to convert DAS records into velocity seismograms via a comparative analysis of DAS and broadband seismometer signals. Further applications for subsurface structural investigations have been proposed, such as receiver function (Yu et al, 2019) and H/V spectral ratio (Spica et al, 2020a) analyses.…”
Section: Main Text Introductionmentioning
confidence: 99%